2010
DOI: 10.1152/jn.00956.2009
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Individual Muscle Mechanical Action From Endpoint Force

Abstract: Kutch JJ, Kuo AD, Rymer WZ. Extraction of individual muscle mechanical action from endpoint force. J Neurophysiol 103: 3535-3546, 2010. First published April 14, 2010 doi:10.1152/jn.00956.2009. Most motor tasks require the simultaneous coordination of multiple muscles. That coordination is poorly understood in part because there is no noninvasive means of isolating a single muscle's contribution to the resultant endpoint force. The contribution of a single motor unit to isometric tasks can, however, be charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…These results indicate that the fluctuations in the index finger movements were distributed not only in the abduction-adduction direction but also in the extension-flexion direction. The index finger movements in various directions in the current study were consistent with those in previous studies in which the isometric forces in several muscles across the MCP joint were demonstrated by fluctuations in abduction-adduction/extension-flexion (Kutch et al, 2008(Kutch et al, , 2010.…”
Section: Larger Fluctuations In Extension-flexion Direction As Comparsupporting
confidence: 91%
See 2 more Smart Citations
“…These results indicate that the fluctuations in the index finger movements were distributed not only in the abduction-adduction direction but also in the extension-flexion direction. The index finger movements in various directions in the current study were consistent with those in previous studies in which the isometric forces in several muscles across the MCP joint were demonstrated by fluctuations in abduction-adduction/extension-flexion (Kutch et al, 2008(Kutch et al, , 2010.…”
Section: Larger Fluctuations In Extension-flexion Direction As Comparsupporting
confidence: 91%
“…Biomechanical (Valero-Cuevas et al, 1998) and neurophysiological approaches (Kutch et al, 2008(Kutch et al, , 2010 demonstrated that the preferred direction of the first dorsal interosseus (FDI) muscle is not complete abduction direction but slightly flexion. FDI can help with that, but it comes at a cost flexion force generated by its flexion moment arm (An et al, 1983).…”
Section: Technique For Measuring Finger Movement In the Two-dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note also that although the experiments described here involved extensive dissections to isolate individual muscles, other less invasive methods of estimating muscle actions have been developed (Kutch et al, 2010). Such less invasive methods might be used in combination with the computational analyses described in this study to construct musculoskeletal models.…”
Section: Developing Musculoskeletal Muscle Models Based On In Situ Mementioning
confidence: 99%
“…In another work of the same research group [18], force contributions of separate muscles to the effort developed by the index finger tip were estimated in a parallel manner with recording of integral EMGs of the muscles involved. In this case, the probable hysteresis phenomenon in EMG activity of the muscles involved in generation of isometric efforts, which was observed in our study, was also not taken into account.…”
Section: Discussionmentioning
confidence: 99%